Evaluación de los equipamientos urbanos al servicio de la industria creativa: caso de estudio Barranquilla (2022)
Over the years, the creative industry has become a preponderant aspect for the economic consolidation of large cities since it allows obtaining greater investment by external entities and increasing the rate of visitors per year, so it can be deducted that the activities that contribute to this industry are key elements for economic success in the modern urban setting. This project assesses the density of the facilities compared to the presence of artistic expressions in the city and exposes the possibility of consolidating Barranquilla as a creative city through the creation of new urban facilities that allow activating the cultural industry in the sectors where they produced cultural production initiatives. The method used allows the assessment of the deficit of these facilities with respect to where the community practices different cultural activities, with georeferential analysis instruments applied to the city, in this way the information provided by Carnaval S.A. is superimposed. and the information collected through the field study. The results make it possible to identify the location of the existing urban facilities, which opens the way for a reassessment of the space and strategic urban transformations. The study carried out shows that Barranquilla does not have a sufficient amount of cultural facilities to meet the demand for artistic manifestations generated by the creative industry, a fact that also affects the local economy, the above opens the way and validates the implementation of facilities as a model of urban territorial intervention.